2019
DOI: 10.3201/eid2508.190526
|View full text |Cite
|
Sign up to set email alerts
|

Sneathia amniiand Maternal Chorioamnionitis and Stillbirth, Mozambique

Abstract: We report a case of Sneathia amnii as the causative agent of maternal chorioamnionitis and congenital pneumonia resulting in a late fetal death in Mozambique, with strong supportive postmortem molecular and histopathologic confirmation. This rare, fastidious gram-negative coccobacillus has been reported to infrequently cause abortions, stillbirths, and neonatal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Previous in vitro studies showed similar cytokine/chemokine profiles for tested BVAB in the context of human vaginal 87 , 124 126 or endometrial epithelial models 108 , 127 . A. vaginae and S. amnii have been also found in patients with inflammatory conditions, such as intrapartum bacteremia 128 , endometritis 129 , urethritis 130 , chorioamnionitis 27 , 131 , and meningitis 132 , further supporting their pathogenic properties. These inflammatory BVAB species may also facilitate acquisition of HIV and other STIs via activation and recruitment of immune cells to the cervical microenvironment 133 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous in vitro studies showed similar cytokine/chemokine profiles for tested BVAB in the context of human vaginal 87 , 124 126 or endometrial epithelial models 108 , 127 . A. vaginae and S. amnii have been also found in patients with inflammatory conditions, such as intrapartum bacteremia 128 , endometritis 129 , urethritis 130 , chorioamnionitis 27 , 131 , and meningitis 132 , further supporting their pathogenic properties. These inflammatory BVAB species may also facilitate acquisition of HIV and other STIs via activation and recruitment of immune cells to the cervical microenvironment 133 .…”
Section: Discussionmentioning
confidence: 86%
“…Intriguingly, the higher risk for preterm labor have been associated with high levels of particular BV-associated bacteria (BVAB), including Sneathia amnii , in vaginal fluids 20 23 . The same BVAB species, S. amnii , has been reported to cause maternal chorioamnionitis, spontaneous abortion, and stillbirth 24 27 .…”
Section: Introductionmentioning
confidence: 94%
“…PCR and other molecular methods have been shown to be useful for the diagnosis of other fastidious organisms that cause disease in neonates such as Mycoplasma hominis , 42 Ureaplasma parvum , 43 Leptotrichia amnionii , 44 and Sneathia amnii . 45 Epidemiological studies of neonatal serious bacterial infections that only use culture-based methods likely underestimate both the number and variety of infections caused by bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports (including ours) have proven the pathogenicity of S. amnii in invasive (mostly gynaecological) infections. S. amnii has been associated with serious obstetric complications, including peripartal bacteraemia [10] and chorioamnionitis, leading to spontaneous abortions and preterm labour [1][2][3][10][11][12][13][14][15][16]. S. amnii has been described as the causative agent of endometritis, salpingitis, tuboovarian abscess and postpartum renal abscess [8,12,17,18].…”
Section: Discussionmentioning
confidence: 99%
“… S. amnii has been associated with serious obstetric complications, including peripartal bacteraemia [10] and chorioamnionitis, leading to spontaneous abortions and preterm labour [1–3, 10–16]. S.…”
Section: Discussionmentioning
confidence: 99%